Infection and Immune Memory: Variables in Robust Protection by Vaccines Against SARS-CoV-2 - Ahluwalia, Pankaj; Vaibhav, Kumar; Ahluwalia, Meenakshi; Mondal, Ashis K.; Sahajpal, Nikhil; Rojiani, Amyn M.; Kolhe, Ravindra (Frontiers in Immunology, 2021)
SARS-CoV-2 is the cause of a recent pandemic that has led to more than 3 million deaths worldwide. Most individuals are asymptomatic or display mild symptoms, which raises an inherent question as to how does the immune response differs from patients manifesting severe disease? During the initial phase of infection, dysregulated effector immune cells such as neutrophils, macrophages, monocytes, megakaryocytes, basophils, eosinophils, erythroid progenitor cells, and Th17 cells can alter the trajectory of an infected patient to severe disease. On the other hand, properly functioning CD4+, CD8+ cells, NK cells, and DCs reduce the disease severity. Detailed understanding of the immune response of convalescent individuals transitioning from the effector phase to the immunogenic memory phase can provide vital clues to understanding essential variables to assess vaccine-induced protection. Although neutralizing antibodies can wane over time, long-lasting B and T memory cells can persist in recovered individuals. The natural immunological memory captures the diverse repertoire of SARS-CoV-2 epitopes after natural infection whereas, currently approved vaccines are based on a single epitope, spike protein. It is essential to understand the nature of the immune response to natural infection to better identify 'correlates of protection' against this disease. This article discusses recent findings regarding immune response against natural infection to SARS-CoV-2 and the nature of immunogenic memory. More precise knowledge of the acute phase of immune response and its transition to immunological memory will contribute to the future design of vaccines and the identification of variables essential to maintain immune protection across diverse populations.